ANALYSIS OF RISK MANAGEMENT COMMITTEE (RMC) ON COMPANY’S ACCOUNTABILITY: THE IMPLICATION OF CORPORATE GOVERNANCE PRACTICES IN INDONESIA’S PROPERTY AND REAL ESTATE - Ang Swat Lin Lindawati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The existence of RMC is one of the best practices of Good Corporate Governance (GCG) implementation. RMC embraces the principle of transparency where the RMC Company discloses information about risk, risk management and RMC supervision. The objective of this research is to examine the correlation between commissioner characteristic, audit committee characteristic, business complexity, and reputation audit firm as the most influential determinant factors to the existence of risk management committee (RMC) towards company accountability in Indonesia’s property and real estate. The population used was property and real estate companies listed in Indonesia Stock Exchange period 2013-2015. The sample was taken by purposive sampling and resulted in the final sample of 75 companies. Data were taken from the companies' annual report and analyzed by logistic regression analysis tools. The result of the logistic regression showed that the size of the board of commissioners and the audit firm's reputation has a positive effect on the existence of RMC, while other variables (independent board of commissioners, board of commissioners meeting frequency, audit committee independence, accounting expertise and finance audit committee, and business complexity) have no effect on RMC existence.